The nexus between financial integration and real economy: Solow-growth model concept - Rahman, Md. Saifur; Shahari, Farihana (Elsevier Ltd, 2017)
This paper aims to investigate the nexus between financial integration and the real economy in ASEAN + 3 economies based on the concept of Solow-Growth Model. The equity indices as a proxy for financial markets are collected from each ASEAN + 3 members and are segmented between two periods; before and after the financial cooperation agreement period. The finding presents several outcomes; 1) no cointegration nexus is found in the system during the pre-agreement periods; 2) the markets are found cointegrated during the post-agreement period, 3) financial integration is found to influence the real sectors of ASEAN + 3 economies. Finally, this study offers policy implications to improve financial integration for stabilizing the real economy.